Exploring chemical disposal options for non-condensable gasses in geothermal power plants: A case study of Kizildere geothermal field (Türkiye) - Haklidir, Fusun S. Tut; Cetin, Raziye Senguen; Kilincarslan, Sanem (Pergamon-Elsevier Science Ltd, 2024)
Geothermal power plants are among the most important renewable energy power plants owing to their highcapacity factors and integrated utilization possibilities. Currently, these power plants utilize geothermal fluid to generate electricity. Although their emissions are lower than those of conventional power plants, gasses such as CO2 and H2S are released into the air from the cooling towers, particularly in flash-type geothermal power plants To reduce the emission of CO2 gas released from geothermal power plants, reinjection studies have mainly been carried out around the world. These types of studies require extensive analysis of underground fracture systems, detailed geosciences, and the reservoir studies. However, these studies are considered risky and expensive for most plant operators because possible changes in underground fracture systems may affect the productivity of geothermal production zones. In terms of the environmental impact, hydrogen sulfide is a more harmful gas than CO2. Effective H2S removal methods cannot be widely used, except in areas with extremely high concentrations, because they commonly incur significant costs for plant operators. Effective H2S removal methods are not widely available except for geothermal sites with high concentrations. The fact that local limit values can be exceeded in geothermal power plants with relatively low H2S concentrations, such as geothermal power plants in T & uuml;rkiye, pushes plant operators to find new low-cost solutions due to high operation costs. For this reason, a treatment method that can be applied at every site and whose cost is not too high has not yet been put forward. However, NaOH is used for this purpose in geothermal fields such as steam-dominated Geyser field to increase the pH values in geothermal wells, which has been producing for a long time. In this study, field tests were carried out with five different chemicals and pure water to examine the reduction of non-condensable gasses in a geothermal power plant located in the Kizildere (Denizli, T & uuml;rkiye) geothermal field, one of the most important geothermal fields in the world. According to this, the capture of these gasses is technically possible using chemical methods, with a performance of up to 70 % observed in CO2 gas capture. However, although it is possible to capture 70 % of non-condensable gasses with such chemical methods, the consumable cost of the operation is quite high.
Keywords: Geothermal Power Plant; Geothermal Fluids; Carbon Dioxide; Hydrogen Sulfide; Gas Disposal